Redescription of Rhipidocotyle jeffersoni (Kohn, 1970) Overstreet & Curran, 2002 (Digenea: Bucephalidae) - Kohn, Anna; Fernandes, Berenice M.m. (Zootaxa, 2006)
Rhipidocotyle jeffersoni (Kohn, 1970) Overstreet & Curran, 2002 is redescribed, based on the holotype and on additional specimens from the intestine of the type-host Salminus brasiliensis (= S. maxillosus) (Characidae), collected at different dates and from several localities of the Paraná River and the hydroelectric power station reservoir of Itaipu, Paraná State, Brazil. Rhipidocotyle jeffersoni is compared with all other species in the genus to confirm its validity. New morphological data, such as different positions of the ovary, testes and caeca, and the extent of the uterus are presented and considered to be specific variations.